2007
DOI: 10.3354/meps07154
|View full text |Cite
|
Sign up to set email alerts
|

Growth and condition indices in juvenile sole Solea solea measured to assess the quality of essential fish habitat

Abstract: ) and highest condition indices (mean K = 1.19; TAG:ST = 2.18) at the Authie, Canche and Somme estuaries. The indices measured in this study correlated well with anthropogenic disturbance and may provide a useful tool to assess habitat quality. Sites with highest sediment chemical contaminants had the lowest habitat quality and, through growth and lipid-storage limitation, could dramatically lower over-winter survival of the juveniles living in these nursery grounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 31 publications
6
89
1
4
Order By: Relevance
“…Comparisons of perturbed and unperturbed habitats help identify useful biological indicators. In a recent study carried out in the Eastern English Channel, Amara et al (2007) showed that shallow coastal nurseries with the highest amount of sediment chemical contaminants had the lowest habitat quality. Sole juveniles (Solea solea) had the slowest growth rate and the lowest condition indices in the Bay of Seine and near industrialized harbour areas (Dunkerque, Calais and Boulogne) and the highest condition indices at the Authie, Canche and Somme coastal areas.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparisons of perturbed and unperturbed habitats help identify useful biological indicators. In a recent study carried out in the Eastern English Channel, Amara et al (2007) showed that shallow coastal nurseries with the highest amount of sediment chemical contaminants had the lowest habitat quality. Sole juveniles (Solea solea) had the slowest growth rate and the lowest condition indices in the Bay of Seine and near industrialized harbour areas (Dunkerque, Calais and Boulogne) and the highest condition indices at the Authie, Canche and Somme coastal areas.…”
Section: Discussionmentioning
confidence: 98%
“…These two estuaries are not impacted by any important human activity and are considered as clean estuaries (Durou et al, 2007;Amara et al, 2007). The Seine estuary is the largest megatidal estuary in the English Channel, covering approximately 150 km 2 at high tide.…”
Section: Study Area and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth is inextricably linked to mortality in the early life stage, which is supported by the general inverse relationship be tween size of an individual fish and its risk of mortality (Zijlstra et al 1982, Beverton & Iles 1992, Sogard 1997. This has motivated the use of fish growth as a suitable index to assess habitat quality (Brandt 1993, Able et al 1999, Le Pape et al 2003, Amara et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Juveniles benefit from the favourable conditions (water temperature, food availability and refuge from predators) in estuarine nursery areas which allow for enhanced growth and survival (Gibson, 1994;Beck et al, 2001). However, they also face demanding environmental conditions, both of natural origin, such as salinity variations and the consequent physiological demands, and human origin, such as pollution loads, which degrade habitat quality and may negatively affect individual fitness, maximum growth rates and ultimately survival (Meng et al, 2001;Amara et al, 2007;Le Pape et al, 2007). Variations in habitat quality, growth and survival during early life history stages influence connectivity with adult subpopulations (Gibson, 1994;van der Veer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%